Sanksi Bagi Guru yang Melakukan Tindak Kekerasan Terhadap Murid Dalam Kegiatan Belajar Mengajar di Kota Prabumulih (Putusan Pengadilan Nomor 44/Pid.Sus/2015/PN.Pbm) - Krisna Brian Adam Putra; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2017)
In Indonesia, the act of mistreatment has been done by a teacher to the students in the school has often happened. The form make physical contact or beating to the limbs of students. Appropriate sanctions are required so that the settlement of violent cases can be resolved thoroughly and fairly. This type of research uses juridical-normative approach with chase approach (case approach) and the source of law is from Court Decision Number 44 / Pid.Sus /2015/PN.Pbm. The results can be concluded, among others, the decision imposed by the court is not in accordance with those contained in the applicable legislation. The way the violent act cannot solve a problem but instead raises a problem for the teacher himself. For teachers who commit acts of violence against their students can not be excluded to be sanctioned.